Bloom : engagement kit designed to encourage social interaction between people with young-onset Alzheimer's - Komari, Amira (2018)
Social interactions that lead to positive affect are fundamental to human wellbeing. It helps improve the quality of life, and fulfils the need to be recognised, accepted and valued as an individual. However, individuals with Alzheimer’s are challenged to achieve positive social interaction. The challenges become most acute when they begin to lose their grip on the present and their present condition. Seeing other fellow people with Alzheimer’s does not necessarily create a forgiving play environment, but rather, the opposite. This results in a common display of agitation and disruptive behaviour, which occurs when the individual’s stress threshold is exceeded. Bloom, is a social engagement kit designed to foster social interaction between people with young-onset Alzheimer’s. The project was developed in partnership with clients at the Family of Wisdom Center run by the Alzheimer’s Disease Association, using a participatory design approach. The kit consists of an interactive board, puzzle pieces as well as conversational cards. The outcomes from the activities provide indicators of wellbeing of the individual with young-onset Alzheimer’s, hence enabling caregivers to gain insight into the state of their loved ones wellbeing.